Consumer Behavior toward Halal Food Using Theory of Planned Behavior and Theory of Interpersonal Behaviors among Muslim Students in Tasikmalaya - Mochamad Shahbaz Van Ahsen; Ratih Hendayani (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2022)
The share of halal products in Indonesia is enormous and grows yearly. With this rapid development, the City of Tasikmalaya plans to become the pioneer of the first halal tourism in West Java by prioritizing halal certification in food. However, the facts on the ground state that many Muslim students still do not understand and tend not to care about consuming halal food. This study aims to reveal the magnitude of the influence of attitudes, subjective norms, perceived behavioral control, religiosity, and habits that are formed on purchase intentions and actual purchases of halal food on Tasikmalaya Muslim Students. The method used in this research is descriptive quantitative by distributing it to 404 respondents. The data analysis technique in this study uses Partial Least Structural Equation Modeling (PLS-SEM). The results show that attitude, subjective norm, perceived behavior, and perceived behavior positively affect purchase intention. Purchase intention and habit positively affect the actual purchase, while habit moderates the relationship between purchase intention. The last, religiosity has a positive effect on attitude and purchase intention. Keywords: Halal Food, Theory of Planned Behavior, Theory of Interpersonal Behavior, Religiosity